Llamas and alpacas in Europe: Endoparasites of the digestive tract and their pharmacotherapeutic control. Issue 3 (June 2015) - Franz, Sonja; Wittek, Thomas; Joachim, Anja; Hinney, Barbara; Dadak, Agnes M.
Highlights Endoparasitosis is a major health concern in llamas and alpacas. There is a lack of studies on safety and efficacy for most anthelmintics. The potential risk of either underdosing or overdosing is high.